Inequality, ICT and financial access in Africa - Vanessa S. Tchamyou; Guido Erreygers; Danny Cassimon (African Governance and Development Institute (AGDI), 2018)
This study investigates the role of information and communication technology (ICT) on income inequality through financial development dynamics of depth (money supply and liquid liabilities), efficiency (at banking and financial system levels), activity (from banking and financial system perspectives) and size, in 48 African countries for the period 1996 to 2014. The empirical evidence is based on Generalised Method of Moments. While both financial depth and size are established to reduce inequality contingent on ICT, only the effect of financial depth in reducing inequality is robust to the inclusion of time invariant variables to the set of strictly exogenous variables. We extend the analysis by decomposing financial depth into its components, namely : formal, informal, semi-formal and non-formal financial sectors. The findings based on this extension show that ICT reduces income inequality through formal financial sector development and financial sector formalization as opposed to informal financial sector development and financial sector informalization. The study contributes at the same time to the macroeconomic literature on measuring financial development and responds to the growing field of addressing post-2015 Sustainable Development Goals (SDGs) inequality challenges by means of ICT and financial access.
Keywords: I30; L96; O16; O55; 330; Inequality; ICT; Financial development; Africa